MENGAQIQAHKAN ORANG YANG SUDAH MENINGGAL MENURUT MADZHAB SYAFI’I DAN MADZHAB HANBALI - Fauri Gunawan; Bitoh Purnomo (Muqaranah, 2021)
Abstract The Law of Imparting People Who Have Died According to the Syafi'I School and the Hanbali School. According to the Shafi'i Madhhab, it is permissible to certify a person who has died, if there is a baby, it is sunnah to be aqiqah. If a parent dies, it is permissible if there is a will from the deceased person. Meanwhile, according to the Hanbali Madzhab, it is permissible to aqiqah a person who has died, be it a baby or an elderly person, as long as the aqiqah is performed in multiples of 7 (a week). And the similarities and differences between the Aqiqah of the Dead According to the Shafi'i and Hanbali schools, the similarities between the two are that they are both an expression of gratitude for the blessings that Allah has given in the form of the birth of a child. When a baby is born, Satan immediately meets him, embraces him, puts him in his hands and tries his best to make him his follower, while the difference between the two is in terms of the law. Meanwhile, in the Hanbali school of law, it is the sunnah of mu'akkad to aqiqah a person who has died. This research is a type of descriptive qualitative research, the method used in this thesis is library research Keywords: Aqiqah, Madzhab Syafi‟i, Mazhab Hanbali